Social Accountability for Adolescent Sexual and Reproductive Health - Panthi, Giri Prasad (Himalayan Journal of Sociology and Anthropology, 2017)
Adolescent population of Nepal is facing health and social problems related to sexual, reproductive, behavioral and traditional social practices. Adolescent pregnancy, child marriage, unwanted pregnancies, Chhaupadhi (restrictions during menstruation and delivery), sexual- gender based violence, unsafe abortion, HIV/AIDS, drug addiction and suicide are major problems which have severe consequences in the lives of adolescents in Nepal. Addressing such daunting problems that adolescents are facing today needs holistic approach, going beyond health. Wider community support, civic engagement and social mobilizations are required to tackle the ASRH problems. Community Based Institutions (CBIs), Community Leaders and citizens have obligations to respond to the problems related with service delivery and ending harmful practice as a social accountability for protection, fulfill and upholding the rights of adolescents. In this context, the objective of this study is assess awareness and engagement capacity of citizens for addressing adolescent sexual and reproductive health problems as a social accountability in Baitadi District of Nepal. Descriptive and analytical research design were used to assess the level of awareness and empowerment from the citizen’ perspectives. A total of 337 respondents affiliated with the five different types of community based institutions (CBIs) were interviewed using structured questionnaire for data collection and data analysis was done by using SPSS version 16.0. The preliminary results of the study reveals that majority of citizens were aware and informed about SRH problems of adolescents, citizens perceived that child-marriage (15%) is the main issue of adolescents in the community followed by Gender Based Violence (13.4%) and adolescent pregnancy (12.7%) among others. The study reveals that citizens belonging to rural areas have more citizen, actions on preventing child marriage; awareness level was higher among citizens from Non-Dalit communities than in Dalit communities. Further, 59.9 percent citizens feel confident to talk about sexual-reproductive health services related concerns in the meeting whereas 32.6 percent citizens perceived that they are hesitant to speak on SRH issues. Similarly, nearly half of the citizens perceived that they were not capable of deciding freely to talk about SRH related issues in the meeting. Only 61.1 percent citizens feel confident to claim for access to quality health service as their fundamental rights from public health facilities. The study concluded that majority of citizens affiliated with Community Based Institutions were aware about characteristics and Sexual and Reproductive Health issues of adolescent population at their communities. However, still a sizeable citizen felt less confident to use their individual agency to decide freely, speaking up against existing traditional norms and shown less confident in claiming Sexual and Reproductive health service as rights. The study revealed that citizen’s accountability capacity is inadequate for tackling adolescent sexual and reproductive health service provision and social behavior change at the community level and therefore this calls for the dire needs to build the capacity of vanguard citizens to contribute to improving adolescents sexual and reproductive health status.Himalayan Journal of Sociology & Anthropology - Vol. VII (2016), page: 13-39